Metal-free catalysis for the reaction of nitrogen dioxide dimer with phenol: An unexpected favorable source of nitrate and aerosol precursors in vehicle exhaust. (March 2022) - Bai, Feng-Yang; Liu, Zi-Yu; Ni, Shuang; Yang, Yong-Sheng; Yu, Zhou; Wang, Guang-Hui; Zhao, Zhen; Pan, Xiu-Mei
Abstract: Atmospheric reaction mechanism and dynamics of phenol with nitrogen dioxide dimer were explored by the density functional theory and high-level quantum chemistry combined with statistical kinetic calculations within 220–800 K. The nitric acid and phenyl nitrite, the typical aerosol precursors, are the preponderant products because of the low formation free energy barrier (∼8.7 kcal/mol) and fast rate constants (∼10 −15 cm 3 molecule −1 s −1 at 298 K). Phenyl nitrate is the minor product and it would be also formed from the transformation of phenyl nitrite in NO2 -rich environment. More importantly, kinetic effects and catalytic mechanism of a series of metal-free catalysts (H2 O, NH3, CH3 NH2, CH3 NHCH3, HCOOH, and CH3 COOH) on the title reaction were investigated at the same level. The results indicate that CH3 NH2 and CH3 NHCH3 can not only catalyze the title reaction by lowering the free energy barrier (about 1.4–6.5 kcal/mol) but also facilitate the production of organic ammonium nitrate via acting as a donor-acceptor of hydrogen. Conversely, the other species are non-catalytic upon the title reaction. The stabilization energies and donor-acceptor interactions in alkali-catalyzed product complexes were explored, which can provide new insights to the properties of aerosol precursors. Moreover, the lifetime of phenol determined by nitrogen dioxide dimer in the presence of dimethylamine may compete with that of determined by OH radicals, indicating that nitrogen dioxide dimer is responsible for the elimination of phenol in the polluted atmosphere. This work could help us thoroughly understand the removal of nitrogen oxides and phenol as well as new aerosol precursor aggregation in vehicle exhaust. Graphical abstract: Image 1 Highlights: Mechanism and kinetics of phenol reaction with NO2 dimer isomers were explored by DFT. Ntric acid and phenyl nitrite are the main products for the reaction of phenol with NO2 dimer. A new alkali-driven homogeneous nucleation mechanism was proposed for the first time. The amines can facilitate phenol reaction with NO2 dimer and organic ammonium production. Water, ammonia, formic and acetic acid do not catalyze the reaction of phenol with NO2 dimer.